Silicon-carbon composite material as well as preparation method and application thereof
By growing silicon nanoparticles inside porous carbon and forming an internal cavity and external carbon shell, the silicon-carbon composite material of lithium-ion battery negative electrode material is solved, and high energy density and long cycle life are achieved Battery performance.
Patent Information
- Application Number
- CN202411670810.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-18
AI Technical Summary
The specific capacity of the negative electrode material of the existing lithium-ion battery is limited, and the silicon-based material expands in large volume, poor conductivity and poor cycle stability during charging and discharging, limiting the energy density and life of the battery.
Silicon-carbon composite material using silicon nanoparticles/cavity@porous carbon@carbon shell layer as the negative electrode material, silicon nanoparticles are grown inside porous carbon by chemical vapor deposition, and internal cavity is formed by impregnation polymerization and high-temperature pyrolysis. External carbon shell, alleviating volume expansion and improving conductivity.
The lithium-ion battery negative electrode material with high energy density and long cycle life has been achieved, and the volume expansion is alleviated through the internal cavity and the external carbon shell is improved in conductivity and stability.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery negative electrode materials, and in particular to a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell layer, and a preparation method and application thereof. Background Art
[0002] The biggest limitation to the development of the global lithium-ion secondary battery industry is the positive and negative electrode materials. The current commercial lithium battery negative electrode material is still graphite, with a specific capacity of 372 mAh / g. Graphite negative electrodes have many advantages in the cycle process: first, the volume expansion is small (<10%), so it can ensure safety during use; second, the raw materials are relatively abundant and cheap. Finally, it is safer and is not prone to thermal runaway and explosion. However, social development requires lithium-ion batteries with longer life and higher specific capacity. At present, the development of graphite negative electrode materials has reached a bottleneck, and the capacity cannot be further improved.
[0003] In order to improve the energy density of lithium-ion batteries, people are committed to finding high-energy negative electrode materials. Among them, silicon-based negative electrode materials have a higher theoretical capacity, which is about 11 times that of graphite negative electrode materials. In addition, silicon-based materials have the following advantages: first, silicon-based materials have a low discharge potential and can output a higher energy density; second, silicon-based materials are abundant on the earth; and finally, silicon-based materials are environmentally friendly and pollution-free. However, there are some problems in the practical application of silicon-based negative electrode materials: (1) Due to the unique lithium storage mechanism of silicon-based materials, there is a large volume expansion during the charging and discharging process; (2) The poor conductivity of silicon-based materials will limit the electron transmission process and the chemical reaction activity of the electrode material; (3) The first coulomb efficiency of silicon-based materials is not high, and a large amount of electrolyte participates in the formation of a solid electrolyte intermediate phase, resulting in a decrease in capacity.
[0004] Chinese patent CN118156450A discloses a porous carbon matrix as the core, in which nano-silicon is deposited by chemical vapor phase, and then coated with a carbon layer on the surface. As a negative electrode material for lithium-ion batteries, the first coulomb efficiency of this material at a rate of 0.1C is about 85.67% to 93.61%, and the first discharge capacity at different discharge cut-off voltages is about 2000mAh / g, but there is no long cycle description, and its electrochemical stability is still not good enough.
[0005] Chinese patent CN118108205A discloses a method of preparing a porous carbon material by thermal reduction reaction using carbon dioxide as a carbon source, and then preparing a silicon-carbon composite material by chemical vapor deposition using the porous carbon material as a precursor. The method provides a unique method for preparing porous carbon and silicon-carbon composite materials. This excellent skeleton structure provides an excellent internal environment for the in-situ growth of nano-silicon, and the skeleton greatly suppresses the volume expansion of the silicon material and improves the electrochemical performance of the composite material. However, the system does not limit the contact between silicon and the electrolyte, and inevitably wastes a large amount of electrolyte to form a solid electrolyte intermediate phase, and the cycle stability is poor. Summary of the invention
[0006] The purpose of the present invention is to solve the above problems in the prior art, and to provide a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell layer and its preparation method and application, the composite material is suitable for use as a negative electrode material for next-generation high-energy lithium-ion batteries, and has extremely high cycle stability. The preparation method of the silicon-carbon composite material provided by the present invention is simple, the production cost is low, the preparation efficiency is high, and the preparation of high-energy negative electrode materials can be achieved in a simple preparation process, which is particularly suitable for industrialized scale-up production.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme:
[0008] A method for preparing a silicon-carbon composite material comprises the following steps:
[0009] 1) placing the porous carbon spheres in a tube furnace, replacing the air in the tube furnace with a protective atmosphere, and then connecting a gaseous silicon source to obtain a composite of porous carbon loaded with silicon nanoparticles by chemical vapor deposition;
[0010] 2) impregnating the composite obtained in step 1) in a monomer capable of initiating polymerization and polymerizing it using an initiator, or in a polymer solution, repeatedly immersing, filtering, washing, and drying for multiple times, and filling the voids of the composite with a polymer material having a low carbonization yield;
[0011] 3) coating the surface of the sample obtained in step 2) with a layer of precursor with high carbonization yield, using a chemical method or a physical method;
[0012] 4) The sample obtained in step 3) is pyrolyzed at high temperature under a protective atmosphere. The polymer material with a low carbonization yield is pyrolyzed into small molecular substances that are released to form pores, and the precursor with a high carbonization yield is pyrolyzed to form an outer carbon shell, thereby obtaining a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell.
[0013] In step 1), the porous carbon spheres have a uniform pore distribution with an average pore size of 0.05 to 0.1 μm.
[0014] In step 1), the gaseous silicon source includes at least one of silane, dichlorosilane, trichlorosilane, silicon tetrachloride and disilane.
[0015] In step 1), different gaseous silicon sources have different reaction temperatures. The reaction temperature of vapor deposition is 400-900°C, the heating rate can be 2-10°C / min, and the reaction time is 0.5-4 h.
[0016] In step 2), the monomers include styrene and styrene derivatives, (meth) acrylic acid and its esters, and vinyl acetate; the initiator adopts a thermal initiator or a photoinitiator; the thermal initiator includes azo compounds, peroxide compounds, ammonium persulfate, potassium persulfate, persulfate, ferric persulfate, sodium persulfate, etc.; the photoinitiator includes benzoin dimethyl ether, α,α-dimethylbenzil ketal, α,α-diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenyl-1-benzophenone, 1-hydroxycyclohexyl benzophenone, benzophenone / tertiary amine, thioxanthone / tertiary amine, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone, etc.
[0017] In step 3), the precursor with high carbonization yield includes at least one of polyacrylonitrile, phenolic resin, polydopamine, biomass polymer, and asphalt.
[0018] In step 3), the coating methods include solution method, thermal decomposition method, spray drying method, mechanical ball milling method, sol-gel method, atomic layer deposition method, and self-assembly method.
[0019] In step 4), the protective atmosphere can be high-purity nitrogen or argon gas, the heating rate is 2 to 10 °C / min, the pyrolysis temperature is 600 to 900 °C, and the time is 1 to 6 h, depending on the specific material requirements.
[0020] A silicon-carbon composite material is prepared by adopting the preparation method.
[0021] An application of a silicon-carbon composite material is used as a negative electrode material for a lithium-ion battery.
[0022] The present invention grows silicon nanoparticles inside the pores of a porous carbon-based material by chemical vapor deposition. Further, a method of impregnation monomer free radical polymerization is adopted to fill the pores of the porous carbon base material with a polymer material that can be completely pyrolyzed at high temperature as a sacrificial layer. A carbon shell precursor with a high carbonization yield is further coated. After a subsequent pyrolysis reaction, an internal cavity layer and an external carbon shell layer can be obtained simultaneously by high-temperature pyrolysis under an inert atmosphere. The composite material is used as a negative electrode material for a lithium-ion battery. The internal voids can buffer the volume expansion of the silicon-based material, the porous carbon skeleton provides excellent conductivity, and the outermost carbon shell layer isolates the direct contact between the silicon-based active material and the electrolyte, effectively improving the coulombic efficiency. The method of the present invention provides a new idea for the preparation of high-performance silicon-carbon composite negative electrodes, and realizes a highly scalable preparation method that can be used for industrial scale-up preparation.
[0023] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0024] The present invention adopts porous carbon-based materials to effectively improve the conductivity of silicon-based materials. Before the sacrificial layer polymer material is coated with the outer carbon shell, it pre-occupies the hole position of the porous carbon. After pyrolysis, it leaves space for the volume expansion of silicon, effectively alleviating the volume expansion problem of the composite material. The presence of the outer carbon shell reduces the specific surface area of the material while also hindering the contact between the electrolyte and the active material, which can reduce the loss of the electrolyte and improve the cycle performance of the battery. In particular, the rigid porous carbon substrate can form a strong restriction layer while providing conductivity, so that the silicon-based material can only expand inward, ensuring the stability of the outer carbon shell, and then maintaining a stable solid electrolyte phase. DETAILED DESCRIPTION
[0025] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with embodiments.
[0026] Example 1
[0027] 1) 10 g of porous carbon substrate material with uniform pore distribution and average pore size between 0.05 μm and 0.1 μm was placed in a tube furnace. High-purity argon gas was first purged three times to replace all the air in the tube furnace and porous carbon with high-purity argon gas;
[0028] 2) The porous carbon prepared in step 1) is used as the substrate material, an inert atmosphere containing 5% silane is used as the silicon source, the temperature is increased to 500°C at a heating rate of 2°C / min and kept for 1 h to obtain a composite of porous carbon with silicon nanoparticles loaded therein;
[0029] 3) impregnating the composite obtained in step 2) into a solution of methyl methacrylate and azobisisobutyronitrile (the ratio of monomer to initiator is 100), then filtering, and heating to initiate polymerization;
[0030] 4) dispersing the sample obtained in step 3) in deionized water, adding ammonia water and hexadecyltrimethylammonium bromide, adding resorcinol and formaldehyde after 30 minutes and reacting at room temperature for 20 hours, and obtaining a composite microsphere sample coated with resorcinol formaldehyde resin by centrifugal vacuum drying;
[0031] 5) The sample obtained in step 4) was pyrolyzed at high temperature in a tube furnace with argon as the protective gas, the heating rate was 2 °C / min, and the temperature was kept at 800 °C for 0.5 h to obtain a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell.
[0032] The silicon-carbon composite material prepared in this example was used as the negative electrode material of the lithium-ion battery, and a constant current charge and discharge test was performed in a half-cell. The sample had a first cycle capacity of 1325 mAh / g at a current density of 0.1 A / g and a room temperature of 25°C, and the first coulombic efficiency was 80%. After 100 cycles, the capacity retention rate was 85%. After multiple cycles, the outer carbon shell remained stable, and the electrode did not fall off.
[0033] Example 2
[0034] 1) Select 10 g of porous carbon substrate material with uniform pore distribution and average pore size between 0.05 μm and 0.1 μm and place it in a tube furnace. First, purge it with high-purity argon three times to replace all the air in the tube furnace and porous carbon with high-purity argon;
[0035] 2) Using the porous carbon prepared in step 1) as the substrate material and an inert atmosphere containing 5% silane as the silicon source, the temperature was raised to 500°C at a heating rate of 4°C / min and kept at this temperature for 2 h to obtain a composite of porous carbon with silicon nanoparticles loaded therein;
[0036] 3) impregnating the composite obtained in step 2) into a solution of styrene and azobisisobutyronitrile (the ratio of monomer to initiator is 200), then filtering, and heating to initiate polymerization;
[0037] 4) ball-milling and dispersing the sample obtained in step 3) together with asphalt having a softening point greater than 200°C;
[0038] 5) The sample obtained in step 4) was pyrolyzed at high temperature in a tubular furnace with argon as the protective gas, the heating rate was 4 °C / min, and the temperature was kept at 800 °C for 1 h to obtain a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell.
[0039] The outer carbon shell of the silicon-carbon composite material prepared in this embodiment remained stable after multiple cycles. In a constant current charge and discharge test in a half-cell, the sample had a first cycle capacity of 1945 mAh / g at a current density of 0.2 A / g and a room temperature of 25°C. The first coulombic efficiency was 70%, and the capacity retention rate after 100 cycles was 80%. After multiple cycles, the outer carbon shell remained stable and the electrode did not fall off.
[0040] Example 3
[0041] 1) Select 5 g of porous carbon substrate material with uniform pore distribution and average pore size between 0.05 μm and 0.1 μm and place it in a tube furnace. First, purge it with high-purity argon three times to replace all the air in the tube furnace and porous carbon with high-purity argon;
[0042] 2) Using the porous carbon prepared in step 1) as the substrate material and an inert atmosphere containing 5% silane as the silicon source, the temperature was raised to 600°C at a heating rate of 5°C / min and kept at this temperature for 4 h to obtain a composite of porous carbon with silicon nanoparticles loaded therein;
[0043] 3) impregnating the composite obtained in step 2) into a solution of styrene and azobisisobutyronitrile (the ratio of monomer to initiator is 150), then filtering, and heating to initiate polymerization;
[0044] 4) The sample obtained in step 3) is ultrasonically dispersed in Tris buffer, dopamine is added and reacted for 24 h, and then centrifugal vacuum drying is performed to obtain a polydopamine-coated composite microsphere sample;
[0045] 5) The sample obtained in step 4) was pyrolyzed at high temperature in a tubular furnace with argon as the protective gas, the heating rate was 5 °C / min, and the temperature was kept at 900 °C for 2 h to obtain a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell.
[0046] The outer carbon shell of the silicon-carbon composite material prepared in this embodiment remained stable after multiple cycles. A constant current charge and discharge test was carried out in a half-cell. The sample had a first-cycle capacity of 2562 mAh / g at a current density of 0.1 A / g, and the capacity retention rate after 50 cycles was 70%.
[0047] Example 4
[0048] 1) 15 g of porous carbon substrate material with uniform pore distribution and average pore size between 0.05 μm and 0.1 μm was placed in a tube furnace, and purged with high-purity argon three times to replace all the air in the tube furnace and porous carbon with high-purity argon;
[0049] 2) Using the porous carbon prepared in step 1) as the substrate material and an inert atmosphere containing 5% silane as the silicon source, the temperature was raised to 500°C at a heating rate of 2°C / min and kept at this temperature for 4 h to obtain a composite of porous carbon with silicon nanoparticles loaded therein;
[0050] 3) The composite obtained in step 2) is immersed in a solution of vinyl acetate and benzoyl peroxide (the ratio of monomer to initiator is 200), then filtered, and heated to initiate polymerization;
[0051] 4) The sample obtained in step 3) was mixed with asphalt having a softening point greater than 200°C and ball-milled for 20 h to obtain an asphalt-coated composite microsphere sample;
[0052] 5) The sample obtained in step 4) was pyrolyzed at high temperature in a tubular furnace with argon as the protective gas, the heating rate was 2 °C / min, and the temperature was kept at 800 °C for 2 h to obtain a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell.
[0053] The outer carbon shell of the silicon-carbon composite material prepared in this embodiment remained stable after multiple cycles. A constant current charge and discharge test was carried out in a half-cell. The sample had a first-cycle capacity of 1937 mAh / g at a current density of 0.2 A / g, and the capacity retention rate after 100 cycles was 80%.
[0054] Example 5
[0055] 1) 15 g of porous carbon substrate material with uniform pore distribution and average pore size between 0.05 μm and 0.1 μm was placed in a tube furnace, and purged with high-purity argon three times to replace all the air in the tube furnace and porous carbon with high-purity argon;
[0056] 2) Using the porous carbon prepared in step 1) as the substrate material and an inert atmosphere containing 5% silane as the silicon source, the temperature was raised to 700°C at a heating rate of 4°C / min and kept at this temperature for 2 h to obtain a composite of porous carbon with silicon nanoparticles loaded therein;
[0057] 3) The composite obtained in step 2) is immersed in a solution of vinyl acetate and azobisisobutyronitrile (the ratio of monomer to initiator is 200), then filtered, and heated to initiate polymerization;
[0058] 4) dispersing the sample obtained in step 3) in dopamine Tris buffer, stirring and reacting at room temperature for 24 h, and filtering to obtain a polydopamine-coated composite microsphere sample;
[0059] 5) The sample obtained in step 4) was pyrolyzed at high temperature in a tubular furnace with argon as the protective gas, the heating rate was 4 °C / min, and the temperature was kept at 900 °C for 1 h to obtain a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell.
[0060] The outer carbon shell of the silicon-carbon composite material prepared in this embodiment remained stable after multiple cycles. A constant current charge and discharge test was carried out in a half-cell. The sample had a first-cycle capacity of 1864 mAh / g at a current density of 0.2 A / g, and the capacity retention rate after 50 cycles was 85%.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: The following steps are involved: 1) placing the porous carbon spheres in a tube furnace, replacing the air in the tube furnace with a protective atmosphere, and then connecting a gaseous silicon source to obtain a composite of porous carbon loaded with silicon nanoparticles by chemical vapor deposition; 2) impregnating the composite obtained in step 1) in a monomer capable of initiating polymerization and polymerizing it using an initiator, or in a polymer solution, repeatedly immersing, filtering, washing, and drying for multiple times, and filling the voids of the composite with a polymer material having a low carbonization yield; 3) coating the surface of the sample obtained in step 2) with a layer of precursor with high carbonization yield, using a chemical method or a physical method; 4) The sample obtained in step 3) is pyrolyzed at high temperature under a protective atmosphere. The polymer material with a low carbonization yield is pyrolyzed into small molecular substances that are released to form pores, and the precursor with a high carbonization yield is pyrolyzed to form an outer carbon shell, thereby obtaining a silicon-carbon composite material of silicon nanoparticles / cavity@porous carbon@carbon shell.
2. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step 1), the porous carbon spheres have a uniform pore distribution with an average pore size of 0.05 to 0.1 μm.
3. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step 1), the gaseous silicon source includes at least one of silane, dichlorosilane, trichlorosilane, silicon tetrachloride and disilane.
4. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step 1), the reaction temperature of the vapor deposition is 400-900°C, and the reaction time is 0.5-4 h.
5. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step 2), the monomers include styrene and styrene derivatives, (meth) acrylic acid and its esters, and vinyl acetate; and the initiator is a thermal initiator or a photoinitiator.
6. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step 3), the precursor with high carbonization yield includes at least one of polyacrylonitrile, phenolic resin, polydopamine, biomass polymer, and asphalt.
7. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step 3), the coating methods include solution method, pyrolysis method, spray drying method, mechanical ball milling method, sol-gel method, atomic layer deposition method, and self-assembly method.
8. The method for preparing a silicon-carbon composite material according to claim 1, characterized in that: In step 4), the pyrolysis temperature is 600-900°C and the time is 1-6 h.
9. A silicon-carbon composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. The use of a silicon-carbon composite material according to claim 9, characterized in that: Used as negative electrode material for lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of porous carbon material and silicon-carbon negative electrode material
CN118108205A
Silicon-carbon negative electrode material for lithium ion battery and preparation method of silicon-carbon negative electrode material
CN118156450A